Differentiated Assessment In EFL Classroom in Indonesia: Prospects and Challenges - Arsyad, Moh. Arsyad; Suadiyatno, Taufik (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
Differentiated assessment has emerged as a pivotal component within the realm of English Language Teaching (ELT), particularly in the culturally diverse landscape of Indonesia. This paper reviews the prospects and challenges associated with implementing differentiated assessment practices in Indonesian EFL classrooms. Indonesia's linguistic diversity, with over 700 languages spoken across 17,000 islands, coupled with ongoing educational reforms, presents both opportunities and obstacles for differentiated assessment adoption. The paper begins by outlining the potential benefits of differentiated assessment in Indonesia, emphasizing its alignment with learner-centred pedagogy and its ability to cater to diverse learning styles and abilities. Through various assessment methods and tasks, educators can provide equitable opportunities for students to showcase their language proficiency while fostering a constructive learning atmosphere. However, the implementation of differentiated assessment faces significant challenges within the Indonesian EFL context. Deeply ingrained traditional evaluation methods, influenced by standardized testing, pose resistance to change. Moreover, infrastructural limitations, including inadequate teacher training and resource constraints, hinder effective implementation. To address these challenges, the paper proposes strategies such as comprehensive teacher training, curriculum adaptations, and community engagement. By equipping educators with the necessary skills and resources, promoting inclusive curriculum design, and fostering collaboration among stakeholders, the adoption of differentiated assessment can be facilitated.